4. Hemoglobin and hematocrit Levels of the Sumatran elephants (Elephas maximus sumatranus) at the Elephant Conservation Center (ECC) of Saree, Aceh Besar - Ayu Andella Agustina; Al Azhar; Nuzul Asmilia; Amiruddin Amiruddin; Arman Sayuti; Sri Wahyuni (Jurnal Medika Veterinaria, 2017)
This research was done to determine the levels of hemoglobin (Hb) and hematocrit (Ht) of the sumatran elephants captivated at the Elephant Conservation Center (ECC) of Saree, Aceh Besar. In this study blood samples were drawn from 16 sumatran elephants at the ECC using EDTA as an anticoagulant. The levels of Hb and Ht were determined using Sahli and micro-hematocrit methods, respectively. Data was analyzed using t-test. The results showed that Hb concentrations in male and female sumatran elephans were 11.74±0.58 g/dL and 11.84±0.55 g/dL, respectively. Hb levels in sumatran elephants aged 10-30 and 30 years old were 11.87±0.56 g/dL and 11.79±0.50 g/dL, respectively. There was no significant different of Hb levels (P0.05) according to sex and age. Ht values in male sumatran elephants were 38.140.79% and significantly lower (P0.05) than that in female sumatran elephants, 42.001.37%. Similar to that of Hb, Ht values in sumatran elephants aged 10-30 and 30 years old, 40.45±1.21% and 40.22±1.48%, respectively, were not significantly different (P0.05). In conclusion, in the sumatran elephants Hb values were not influenced by sex and age, but Ht values were influenced by sex.